KOMUNITAS BELAJAR MAHASISWA SEMESTER III PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA DALAM PEMBELAJARAN KETERAMPILAN MEMBACA MELALUI KEGIATAN LESSON STUDY - Nur Mei Ningsih (Edukasi Lingua Sastra, 2018)
To improve process of eduacation quality needs inovation that should be done continuously. One of those inovations is by changing the learning paradigm from teacher centered to student centered. So, from this learning is not only focus on students but also how the teacher teaches. One of improvement models to improve the teacher is through lesson study. Lesson study is a creation model of teacher profession collaboratively and continously, based on collegiality principle that helps each others in learning to build learning community (democartics, openness, and continue). Learning community at the third semester students of STKIP Muhammadiyah is quite good, it looks during learning process of reading subject, they look active, and also they are entusistics to understand the material given. It is done with the member of their group, they can also discuss with another group, but it was found that there are three students who have different attitude with another. It was also one student from second group that did not have motivation during learning process, he is A, and from first group is B, and from third group is Lilik, but the lecturer always guided them because they lack of motivation and interest during discussion, it based on the observation from observers, finnaly it can give suggestion for the lecturer to be better in teaching reading.